Analysis of drug related electrolyte disturbances in emergency medicine department - Shah, Karan B.; Gupta, Sapna D.; Rana, Devang A.; Malhotra, Supriya D.; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Electrolytes play an important role in various physiological functions of the body. Electrolyte disturbances are one of the most common problems encountered in critically ill patients. Drugs are also known to cause adverse electrolyte consequences. These drugs could be anti-hypertensive agents, hormones, antipsychotics or steroids. There is paucity of published literature on electrolyte disturbances caused by drugs. The purpose of our study was to evaluate the electrolyte disturbances caused by various drugs in critically ill patients. Methods: Following approval of the Institutional Ethics Committee, data collection was started. Adverse Drug Reactions (ADRs) presenting as an electrolyte disturbance in emergency medicine department or occurring in hospitalized patients in the Intensive care unit (ICU) of our hospital was be collected. ADRs resulting into electrolyte disturbances were identified and analysed in detail for demographic details, types of electrolyte disturbances, seriousness, severity, causality and preventability of ADRs. Fisher's exact test was done to find out the statistical difference between the electrolyte disturbances and different drugs. Results: Total 58 ADRs were reported as an electrolyte disturbance. Mean age of the patients affected was 52.48 years. Highest number of ADRs were observed in the age group of 61 to 70 years. Hypokalemia constituted 32 cases (55.2%) followed by hyponatremia (25.9%), hyperkalemia (6.9%), hypernatremia (6.9%), hypocalcemia (1.7%), hypomagnesemia (1.7%) and hypophosphatemia (1.7%). Insulin was associated with maximum cases of ADRs (27.6%). Conclusions: Electrolyte disturbances constitutes a major chunk of ADRs especially in critically ill patients. The physicians must be well-versed with the dynamics of fluid-electrolyte balance.